2022
DOI: 10.1002/anie.202208204
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Aryldifluoromethylation of Aryl Halides with Aryldifluoromethyl Trimethylsilanes

Abstract: Diaryl difluoromethanes are valuable targets for medicinal chemistry because they are bioisosteres of diaryl ethers and can function as replacements for diaryl methane, ketone, and sulfone groups. However, methods to prepare diaryl difluoromethanes are scarce, especially methods starting from abundant aryl halides. We report the Pd-catalyzed aryldifluoromethylation of aryl halides with aryldifluoromethyl trimethylsilanes (TMSCF 2 Ar). The reaction occurs when the catalyst contains a simple, but unusual, dialky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 74 publications
1
11
0
Order By: Relevance
“…Thus, the more the color tends to the blue region, the stronger and more stable the interaction. [ 32 ] As shown in Figure a and Figure S10 (Supporting Information), it can be seen that the PF 6 − pseudohalides have strong covalent bonding interactions, and the whole interaction changes significantly with its introduction into the structure of MFPs. Particularly, the color between the X‐site, the B‐site, and the A‐site is more blue, indicating an enhanced hydrogen bonding.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the more the color tends to the blue region, the stronger and more stable the interaction. [ 32 ] As shown in Figure a and Figure S10 (Supporting Information), it can be seen that the PF 6 − pseudohalides have strong covalent bonding interactions, and the whole interaction changes significantly with its introduction into the structure of MFPs. Particularly, the color between the X‐site, the B‐site, and the A‐site is more blue, indicating an enhanced hydrogen bonding.…”
Section: Resultsmentioning
confidence: 99%
“…30–32 Unlike the –CF 3 group, orthogonal nucleophilic methodologies to install –CF 2 Ar groups remain largely underdeveloped. 33–36 We anticipated that a Lewis-acidic boron based scaffold could provide broad routes to related compounds with –CF 2 Ar functionality.…”
mentioning
confidence: 99%
“…Having confirmed that our computational method accurately predicts the barriers to reductive elimination from Pd­(aryl)­(fluoroalkyl) complexes, we investigated the effect of the identity of the fluoroalkyl ligand on the barrier to reductive elimination. We selected Pd complexes containing the aryldialkylphosphine ligand di- tert -butyl­(2-methoxyphenyl)­phosphine ( L ) as the model system because our group recently showed that Pd complexes containing L catalyzed the aryldifluoromethylation of aryl halides with high yields and a broad scope (Scheme (a)). , Other aryldialkylphoshines containing alkoxyaryl moieties such as BrettPhos, RuPhos, and SPhos also have been reported to facilitate a variety of Pd-catalyzed fluoroalkylation reactions; ,, however, we did not investigate systems containing these ligands due to their large sizes and accompanying high computational costs. …”
Section: Resultsmentioning
confidence: 99%
“…We recently suggested that a donor−acceptor interaction between the d orbitals of Pd and a π* orbital of the R F fragment was present in the transition states for reductive elimination from aryl(3-fluorooxindolyl)-and aryl-(difluoromethylaryl)palladium complexes. 12,47 Thus, we hypothesized that the lack of correlation between ΔG ‡ (R F ) and Q(R F ) could result from the presence or absence of such interactions within cis-Pd-TS-R F complexes containing different R F ligands. Indeed, the data points can be partitioned into two subsets that individually correlate ΔG ‡ (R F ) more strongly with Q(R F ): a lower-energy subset A (R 2 = 0.831), in which the R F ligands contain unsaturated groups or hydrogen atoms attached to the α-carbon atom (Figure 4(b), orange triangles), and a higher energy subset B (R 2 = 0.932), in which the R F 5).…”
Section: Quantification Of the Electronic Properties Of Fluoroalkyl L...mentioning
confidence: 99%